2017
DOI: 10.1590/1678-457x.19416
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value of huitlacoche, maize mushroom caused by Ustilago maydis

Abstract: Smutty maize cobs, caused by Ustilago maydis ((DC) Corda.), a fungus belonging to Basidiomycetes, can be seen wherever maize is grown. It is considered as a fungal disease limiting maize yield worldwide. However, in Mesoamerica, it is called as "huitlacoche" and evaluated as an edible mushroom. The present study was conducted to examine nutritional characteristics of this mushroom. In the study, smutty cobs naturally infected by U. maydis were randomly gleaned from plants in maize producing areas in the Medite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 23 publications
0
20
1
Order By: Relevance
“…The energy supply was calculated, reaching a value of 248.53 cal/100 g. In comparison to other studies related to chemical characterization of huitlacoche, Beas, Loarca, Guzmán, Rodriguez, Vasco, & Guevara (2011) , reported an average protein content of 12.4%, 2.9% of crude fat, moisture of 80–86%, total dietary fibre of 54–65%, insoluble dietary fibre of 47–49% and soluble dietary fibre of 8.6–12.5%. From their findings, Aydoğdu & Gölükçü (2017) cited 90% of moisture, 12% of crude protein, 1.8% of total fat and 45% of carbohydrate. The differences observed for the chemical composition of huitlacoche are attributed to the variety of maize and the state of development in which the fungus is harvested, as well as agronomic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy supply was calculated, reaching a value of 248.53 cal/100 g. In comparison to other studies related to chemical characterization of huitlacoche, Beas, Loarca, Guzmán, Rodriguez, Vasco, & Guevara (2011) , reported an average protein content of 12.4%, 2.9% of crude fat, moisture of 80–86%, total dietary fibre of 54–65%, insoluble dietary fibre of 47–49% and soluble dietary fibre of 8.6–12.5%. From their findings, Aydoğdu & Gölükçü (2017) cited 90% of moisture, 12% of crude protein, 1.8% of total fat and 45% of carbohydrate. The differences observed for the chemical composition of huitlacoche are attributed to the variety of maize and the state of development in which the fungus is harvested, as well as agronomic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to other studies, Beas, Loarca, Guzmán, Rodriguez, Vasco, & Guevara, (2011) , reported soluble phenols at a range of 390–640 mg GAE/100 g. When their methanolic extracts were compared to the commercial antioxidant BHT, the authors referred a higher antiradical activity. Aydoğdu & Gölükçü (2017) quantified a total phenolic matter of 113.11 mg GAE/kg dry sample, antioxidant activity, IC50 of 186.44 mg/mg DPPH, for 10 mL methanol:water (80:20) extracts after 1 h at 180 rpm. Salazar-López, Martínez-Saldaña, Reynoso-Camacho, Chávez-Morales, Sandoval-Cardoso, & Guevara-Lara, (2017) , reported two groups of ethanolic extracts: non-concentrated and concentrated.…”
Section: Resultsmentioning
confidence: 99%
“…The fungus is sometimes called "huitlacoche", "maizteca mushroom", "Mexican truffle", "Azteca Caviar" due to its unique, unusual flavour. Young smut galls are edible and treated as delicacy in Latin American countries and Turkey [5,22]. Moreover, given its high content of bioactive compounds, the species exhibits health-enhancing properties [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Young smut galls are edible and treated as delicacy in Latin American countries and Turkey [5,22]. Moreover, given its high content of bioactive compounds, the species exhibits health-enhancing properties [22,23]. It contains large amounts of protein (12% dry base) and low-fat content (up to 6.5 % dry base); hence, it can be used in vegetarian and low-calorie diets [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation